A review of the efficacy of weight training aids. - Church, J.; Allen, T.; Allen, G. W. (Strength and Conditioning Journal, 2016)
This article will review the efficacy of several different weight training aids that are available for use by recreational weight trainers and also competitive athletes in the sports of weightlifting and powerlifting. Some of these aids have been investigated by researchers while information regarding the use of others has been left to practical experience. This review will discuss the use and effectiveness of many weight training aids, thereby offering practitioners the ability to make an informed decision on their use.